671. Relevance of Levofloxacin-Resistant MRSA and hVISA when utilizing directed antibiotic locks to treat stage 4 biofilm bone and joint infections. (15th December 2022) - Vicent, Martie; Daffinee, Kathryn E; Daffinee, Kathryn E; Daffinee, Kathryn E; Daffinee, Kathryn E; Daffinee, Kathryn E; LaPlante, Kerry L
Abstract: Background: Directed antibiotic locks have the potential to treat orthopedic infections due to the ability to bypass specific systemic absorption allowing for higher antimicrobial concentrations. With limiting antimicrobial options to treat biofilm commonly associated with bone and joint infections, our aim is to understand and further test the relevance of utilizing standard systemic MIC values to direct therapy. Methods: Using our previously described biofilm assay with six unique spa-type (t004, t018, t062, t064, t1340, t008) MRSA isolates, biofilm was grown for 4, 6, and 24hrs at 6 log10 CFU/mL in TSB per CLSI guidance adding dextrose 1.25% for biofilm promotion. MIC were run using CLSI guidance. Planktonic cells were removed by irrigation, simulating debridement. 24hr treatment assays, simulating antibiotic locks included levofloxacin (5 mg/mL) in d5W solution and vancomycin (5 mg/mL) in NS. Results: Levofloxacin by definition of standard MIC values was found to be resistant in five out of the six MRSA isolates (MIC ranging from 1 – 312mcg.mL). However, at 16-25, 000 times the MIC, levofloxacin demonstrated a decrease in biofilm growth on mature 24-hr established biofilm by 9-130%. Similarly, vancomycin heterogeneous vancomycin-intermediate Staphylococcus aureus (hVISA), at 3000-6000 the MIC demonstrated a decrease of 53-190% mature biofilm growth. Conclusion: All isolates produced consistent biofilm as previously tested as a low or high biofilm-producer when there was no antibiotic present. Levofloxacin and vancomycin at least 1000X the MIC nearly eradicated all established MRSA biofilm. Our next steps will be to evaluate if the MIC values have any effect on additional antibiotics in a lock solution. Disclosures: Kerry L. LaPlante, Pharm.D., FCCP, FIDSA, FIDP, AbbVie Inc.: Grant/Research Support|Gilead Sciences, Inc.: Grant/Research Support|Melinta Therapeutics, Inc., : Grant/Research Support|Merck & Co., Inc.: Advisor/Consultant|Merck & Co., Inc.: Grant/Research Support|Nabriva Therapeutics US, Inc., : Grant/Research Support|Ocean Spray Cranberries, Inc.: Grant/Research Support|Pfizer Pharmaceuticals: Grant/Research Support|Shionogi, Inc.: Grant/Research Support|Tetraphase Pharmaceuticals.: Grant/Research Support.